A Rare Case of Gastric Myiasis in a Lion Caused by Gasterophilus intestinalis (Diptera: Gasterophilidae)-Case Report - Maryam Ganjali; Mojtaba Keighobadi (Tehran University of Medical Sciences, 2016)
Myiasis is the infection caused by a variety of dipterous (fly) larvae in vertebrate's tissue (man and domestic or wild animals). Species of Gasterophilus are obligate parasite of horses, donkeys, zebras, elephants and rhinoceroses. There are records worldwide, but mostly, in tropical and subtropical regions. This case report describes a type of gastric myiasis caused by G. intestinalis in an old lion in a zoo in Sistan, southeast Iran. Myiasis in lions is rarely reported and this is the first report of gastric myiasis in lion.